Educational Services Marketing Management Model in Improving the Brand Image of Islamic Boarding Schools - Sain, Muhammad; Halik, Abdul; Yusuf, Syarifuddin; Ahmad, Jamaluddin; Hamid, Abdul (Al-Ulum, 2025)
This study analyzes the educational services marketing model in improving the brand image of the Al Ikhlash Lampoko Modern at Islamic Boarding School. This type of research is qualitative with a grounded theory approach. Data sources are the leadership of the foundation, the boarding school, teachers, staff, and students. Data analysis is carried out through five systematic stages, namely problem formulation, theoretical review, data collection, analysis, and conclusion drawing. The results of the study indicate that educational services marketing is carried out in an integrated manner, utilizing digital technology through social media and websites, as well as direct marketing support through social activities and interpersonal communication. This strategy effectively strengthens the brand image with targeted geographic, demographic, and psychographic market segmentation. Digital marketing has been proven to expand the reach of the Islamic boarding school, support external recognition, and increase public trust through an emphasis on character education and student skill development. Regular evaluation is essential to maintain the sustainability of service quality.